A inserção e atuação do assistente social nos Centros de Atenção Psicossocial para Álcool e Drogas CAPSad - Tuon, Regina Esther de Araujo Celeguim (2011)
The aim of this work is to analyze the insertion and performance of Social Workers in the Center of Psychosocial Attention for alcohol and other drugs- CAPSad, a community-based outpatient service, created by the Ministry of Health in 2002 to treat individuals with disorders related to the use of psychotropic substances. The starting point of this analysis was a qualitative research carried out from July to December 2010, with social workers of the CAPSad units in the State of São Paulo. The content of their statements made it possible to analyze the practice of social workers regarding the following aspects: daily routine in the institution; specificities of the Social Work in the CAPSad; relation between the Social Worker and other areas of knowledge, and the critical view this professional has of CAPSad. From the analysis of the empirical categories it was possible to conclude that Social Workers play a fundamental and strategic role in this institution, since they work with people from a broader perspective, thus allowing the suffering of the individual with psychotropic substance-related problems to be understood within a historical, social and cultural context. The study also points to the need of Social Workers to enlarge and improve their competences for the institutional work from the perspective of interdisciplinarity